Thomas's Massachusetts, Connecticut, Rhode-Island, Newhampshire & Vermont Almanack, With an Ephemeris, for the Year of our Lord 1797: Being the First after Bissextile, or Leap Year, and Twentyfirst of the Independence of United Columbia. - Thomas, Isaiah, 1749-1831. (Tufts University. Tisch Library., 2018)
24 leaves [Tisch Library copy is bound with an additional front and back leaf and contains handwritten annotations]. Essay and narrative content includes: Address of the President of these States.